PEMANFAATAN MEDIA GEOSPASIAL UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR MATA PELAJARAN GEOGRAFI - Arif Pujianto; Pargito Pargito; Buchori Asyik (Jurnal Studi Sosial / Journal of Social Studies, 2013)
This study aims to improve the activity and the learning achievement of students in the geography subjects by using geospatial media. This action research conducted in SMA Negeri 1 Metro in the second semester of academic year 2011-2012, Grade 12 IPS 1 with of 17 learners. The data was collected through observation by collaborators, with observation instruments. The instrument that used are observation and assessment for observing the activity of the learner. Meanwhile the instruments aim to observing the teacher’s ability in making plan and implementing in the teaching and learning processs. Activities and achievements of learners from cycle 1 to cycle 3 showed good progress. Learners activities were indicated from observations on the learning process, that leads to positive change in cycle 3, where there is no more passive learners. All learners did activities that support the learning process, and could utilize geospatial media by using netbooks and mobile phones. For the achievement of learners showed by good improvement. The researchers stop the action research, and can be concluded that the use of geospatial media can enhance the activity and the learning achievement of students geographic subjects in SMA Negeri 1 Metro.Keywords: geospatial media, activities, achievements